Perspective of older African-American and Non-Hispanic white breast cancer survivors from diverse socioeconomic backgrounds toward physical activity: A qualitative study. Issue 3 (May 2018) - Owusu, Cynthia; Antognoli, Elizabeth; Nock, Nora; Hergenroeder, Paul; Austin, Kristina; Bennet, Elizabeth; Berger, Nathan A.; Cerne, Stephen; Foraker, Katelyn; Heine, Kevin; Heyman, Ellen; Moore, Halle; et al.
Abstract: Background: We sought to explore the perspective of older breast cancer survivors (BCS) from diverse racial and socioeconomic backgrounds toward physical activity (PA) to inform the design of a PA program that fosters acceptability. Methods: Participants included sixty women, ≥ 65 years, within two years of treatment completion for stage I-III breast cancer. We purposely sampled ≥ ten patients in each race [African-American (AA) and Non-Hispanic White (NHW)] and socioeconomic status (SES) [SES disadvantaged and SES non-disadvantaged] group. Participants completed in-person interviews (n = 60) and follow-up focus groups (n = 45). Thematic analyses were employed. Results: The median age was 71.0 years (range: 65–87 years). Five themes emerged: 1) importance of PA; 2) current PA participants engaged in; 3) influence of race and culture on PA attitudes and beliefs; 4) barriers to PA and facilitators to PA; and 5) PA preferences. Barriers included health issues (43%), particularly cancer treatment side effects such as fatigue. Facilitators included religious faith (38%) and family (50%). Preferences included group exercise (97%) and strength training (80%) due to concerns participants had with diminished upper body strength after cancer treatment. Although AA (59%) and SES non-disadvantaged (78%) participants reported that race and culture influenced their attitudes toward PA, it did not translate to racial and SES differences in preferences. Conclusion: Among older BCS, physical activity preferences were shaped by cancer experience, rather than by race and SES. Physical activity programs for older BCS should focus on addressing cancer treatment-related concerns and should include strength training to ensure PA programs are more acceptable to older BCS.